2010
DOI: 10.1262/jrd.09-166n
|View full text |Cite
|
Sign up to set email alerts
|

TGF-.BETA.1 System in Leydig Cells. Part I: Effect of hCG and Progesterone

Abstract: Abstract. Transforming growth factor beta 1 (TGF-β1) modulates male reproductive function. Genetically modified mice overexpressing α/β subunits of hCG (hCG+) show Leydig cell hyperplasia/hypertrophy at prepuberty that disappears as the mice approach adulthood. In this study we analyzed the gene expression of TGF-β1, its specific receptors, type II (TGF-βRII) and type I (activin receptor-like kinase 1 and 5: ALK1 and ALK5), and co-receptor endoglin (CD105) in purified Leydig cells from hCG+ and wild-type mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Progesterone alone did not modify PCNA immunodetection; however, it has been observed that progesterone stimulates endoglin gene expression in mouse Leydig cells [17]. Moreover, incubation of Leydig cells with TGF-β1 and progesterone diminished the expression of Bax (pro-apoptotic gene) without any modification of Bcl-2 (anti apoptotic gene) expression, causing a lower Bax/Bcl-2 ratio compared with the control treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Progesterone alone did not modify PCNA immunodetection; however, it has been observed that progesterone stimulates endoglin gene expression in mouse Leydig cells [17]. Moreover, incubation of Leydig cells with TGF-β1 and progesterone diminished the expression of Bax (pro-apoptotic gene) without any modification of Bcl-2 (anti apoptotic gene) expression, causing a lower Bax/Bcl-2 ratio compared with the control treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, we have described the hormonal regulation of TGF-β1 system in an experimental model [41] and that the in vitro effect of TGF-β1 on mouse Leydig cell induces Smad 1/5 phosphorylation and proliferation markers (Bax/Bcl-2 ratio, PCNA) [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that PR was expressed in a few peritubular and interstitial cells, but not in germ cells of human and nonhuman primates (Luetjens et al, 2006). PR has been shown to be present in rodent Leydig cells (Pino & Valladares, 1988;El-Hefnawy et al, 2000;Gonzalez et al, 2010). In this study, we examined the PR localization in mouse testes by detecting PR promoter driven b-gal expression, and demonstrated that intratesticular hormonal deprivation resulted in PR promoter driven LacZ expression predominantly in Leydig cells.…”
Section: Discussionmentioning
confidence: 86%